What is happening where? An evaluation of social sciences research trends in Nunavut (2004-2019) - Alexis Polidoro; Natalie Carter; Gita Ljubicic; Alison Perrin; Jamal Shirley (Canadian Science Publishing, 2024)
Research licensing administered by the Nunavut Research Institute (NRI) affords Nunavummiut (people of Nunavut) an opportunity to engage in research. The NRI partnered with researchers at McMaster and Carleton Universities to investigate social sciences research licensed between 2004 and 2019. This partnership aimed to understand the scope of research trends in Nunavut. Thematic content analysis was used to (i) identify research topics in social sciences and Inuit knowledge projects; (ii) determine frequency and diversity of topics according to leadership, location, and timeframe; (iii) develop metrics to improve tracking of research; and (iv) contribute to the development of a Nunavut research portal making NRI research applications and reports public. Social sciences research increased during the 16-year study period. Projects were predominantly led by Canadian academics. The highest intensity of research occurred in Iqaluit, and the lowest intensity in Grise Fiord. Social sciences research was mainly focused on topics related to Inuit culture and knowledge. Social scientists most often conducted research using interviews and shared their work via peer-reviewed journal articles. This project is a starting point in raising awareness about research trends for Nunavummiut. This work aims to contribute to broader efforts in developing Nunavut-specific approaches to achieving Inuit self-determination in research.